DAMPAK SERTIFIKASI DAN KOMPETENSI TERHADAP KINERJA DOSEN TETAP YAYASAN DI KOTA BATAM - Sri Langgeng Ratnasari; Ervin Nora Susanti; Widodo Ismanto; Rona Tanjung; Gandhi Sutjahjo (Politeknik Negeri Batam, 2021)
Lecturer performance is an interesting topic to research, because lecturer performance is closely related to higher education performance, therefore lecturer performance must always be improved. This study aims to determine and analyze the impact of certification and competence partially or simultaneously. This type of research is quantitative research. The population of this research is 327 permanent lecturers of the Foundation who have been certified at a private university in Batam, with the sampling technique using a census. The research sample consisted of 327 lecturers, but after the questionnaires were distributed, only 250 lecturers were filled. Data were analyzed using Multiple Linear Regression with SPSS. The results of this study state that certification has a significant impact on lecturer performance, competence has a significant impact on lecturer performance, certification and competence has a significant impact on lecturer performance.